2019
DOI: 10.1038/s41598-019-46657-z
|View full text |Cite
|
Sign up to set email alerts
|

LC3-positive structures are prominent in autophagy-deficient cells

Abstract: Autophagy is an evolutionarily conserved process across eukaryotes that degrades cargoes like aggregate-prone proteins, pathogens, damaged organelles and macromolecules via delivery to lysosomes. The process involves the formation of double-membraned autophagosomes that engulf the cargoes destined for degradation, sometimes with the help of autophagy receptors like p62, which are themselves autophagy substrates. LC3-II, a standard marker for autophagosomes, is generated by the conjugation of cytosolic LC3-I to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
208
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(220 citation statements)
references
References 21 publications
10
208
1
1
Order By: Relevance
“…Activation of autophagy is associated with an increase in LC3-II and decrease in p62 protein [43]. In addition, p62 acts as a platform for LC3-positive structures via binding to LC3-I proteins in the cells [83], making both LC3 and p62 valuable markers of autophagy [84]. However, we did not observe any Western blot signal for p62 protein in our study.…”
Section: Discussioncontrasting
confidence: 77%
“…Activation of autophagy is associated with an increase in LC3-II and decrease in p62 protein [43]. In addition, p62 acts as a platform for LC3-positive structures via binding to LC3-I proteins in the cells [83], making both LC3 and p62 valuable markers of autophagy [84]. However, we did not observe any Western blot signal for p62 protein in our study.…”
Section: Discussioncontrasting
confidence: 77%
“…This occurs even with transient and incomplete inhibition of autophagosome biogenesis. This phenomenon is due to LC3-I sequestration to p62 aggregates, which accumulate when autophagy is impaired [28]. In this study, we found negative correlations between LC3B levels in the renal cortex and the volume density of lysosomes and autolysosomes in the podocytes.…”
Section: Suppression Of Renal Autophagy In Diabetes: Markers and Mechmentioning
confidence: 49%
“…LC3-II is generated by the conjugation of cytosolic LC3-I to phosphatidylethanolamine on the surface of nascent autophagosomes. Accordingly, LC3-II is relatively specifically associated with autophagosomes and autolysosomes [28]. In previous studies, both a decrease in LC3-II/LC3-I ratio [29,30] and an increase in LC3-I/II expression [31] in the kidneys of db/db mice was reported.…”
Section: Suppression Of Renal Autophagy In Diabetes: Markers and Mechmentioning
confidence: 89%
“…In some cases, these structures had two double membranes and could represent autophagosome-like vesicles produced in a TgATG9independent manner. Although ATG9 is required for efficient autophagy, alternative vesicle and puncta formation has been found to occur in other eukaryotic organisms in which ATG9 has been knocked out or silenced (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%